PERAN TEKNOLOGI DALAM TRANSFORMASI EKONOMI DAN BISNIS DI ERA DIGITAL - Dawam Sahrin Najah. S; Rusdi Hidayat N.; Maharani Ikaningtyas; Muhammad Ryan N.Z; Sabrina Indira (CV. KAMPUS AKADEMIK PUBLISING, 2024)
The development of information and communication technology has triggered significant economic and business transformation in the current digital era. In an era where digital connectivity has become the norm, the role of technology in economic and business transformation cannot be underestimated. This article provides an overview of how technology plays a key role in changing the economic and business landscape. Technology facilitates the creation of a digital ecosystem that enables faster and more efficient interactions between businesses, consumers, and markets. The internet and online platforms have opened doors for global market penetration, allowing companies to reach a wider audience and expand their business reach. Furthermore, technology is also changing the way businesses operate through the adoption of digital solutions such as e-commerce, big data analytics, and artificial intelligence. These innovations enable companies to optimize their operational processes, improve efficiency, and create added value for their customers. However, with the various opportunities offered by technology, new challenges also arise. One of them is the need for data security and privacy in an increasingly connected digital environment. Additionally, companies must be prepared to face changes in business models and competition driven by technology.